Hybrid Cross-Linked Chitosan/Protonated-Proline:Glucose Des Membranes with Superior Pervaporation Performance for Ethanol Dehydration - Araya-Lopez, C (ELSEVIER, 2022)
This work explores a protonated L-proline:glucose (molar ratio 5:1) deep eutectic solvent (DES) in fabricating biopolymer membranes utilizing chitosan (CS). Initially, the miscibility of CS and DES to prepare homogeneous dense blend membranes has been investigated. Different techniques, such as scanning electron microscopy, contact angle (CA), atomic force microscopy (AFM), Fourier transformed infrared spectroscopy (FTIR) and swelling degree (uptake), were used to characterize the structure of the resulting membranes. Within the pervaporation performance for ethanol dehydration, Arrhenius and mass transfer analysis were analysed in detail. Interestingly, the addition of DESs provided superior performance to crosslinked CS: DES membranes compared with the ones lacking DES. Based on the morphology and properties observed, this new concept of CS-based membranes can be alternatively applied in other solvent separations requiring hydrophilic membranes. (C) 2022 Elsevier B.V. All rights reserved.